Quantitative assessment of the effects of official match on physical performance factors on under-16 and under-18 female basketball players at national league level - Izquierdo, J. M.; Redondo, J. C. (European Journal of Human Movement, 2021)
This study was aimed at analysing and quantifying relevant effects of competition on performance factors in female basketball players (16.45±0.92 years) with reference to age (under-16 and under-18) and playing positions: guards (n=19), forwards (n=27) and centres (n=22). Participants completed tests to measure jump capacity (countermovement jump-CMJ) and sprint times (10 m and 20 m) at three moments: just before the match (T1), at half-time and after the match (T3). Associated with the increases of perceived effort, results showed "very likely" negative effects with performance decreased from T1-T3 in 20 m (4.03% and 3.51% for guards u-16 and u-18, respectively) and CMJ (15.17% and 13.7% for guards u-16 and forwards u-18, respectively). We only found a "large" ES in T2-T3 in guards u-16 in CMJ. Findings highlight the necessity to customize training, considering requirements and demands of different ages and playing positions to decrease the impact of fatigue after match.